Strategies for Resistance: A Study on Black Mothering as Practices of Disruption for the Schooling of Black children - Brady, Janelle (Journal of the Motherhood Initiative for Research and Community Involvement, 2022)
Black student learners in Greater Toronto Area (GTA) schools face a host of barriers to fair and equitable education. Research has demonstrated that Black students have higher rates of suspension and expulsion (James and Turner 35-37), have lower expectations, face more severe punishment and are ultimately “pushed out” of schools (Dei et al. 10). Black mothers have long employed resistance strategies to combat such barriers, such as navigating race and racial microaggressions (Allen and White-Smith 412), racial and class socializing of their children (Turner 248), and developing an overall understanding of how race impacts their children’s education (Williams et al. 937). Much of the literature on Black mothers’ experiences and effective social and political mobilization comes from an American perspective, and thus further investigation of such action in the Canadian context is warranted. This article draws on findings from a doctoral dissertation project on Black mothering experiences in the kindergarten to grade 12 (K-12) education system. Thirty-three mothers, primarily from the Jane and Finch community in the GTA, participated in three focus groups and three one-on-one interviews. Using a Black feminist theoretical framework, this article focuses on three key study findings: the systemic racism faced by student learners, the intersectional systemic racism faced by Black mothers, and the resistance strategies employed by Black mothers. By analyzing the data emerging from this qualitative research, this article explores the resistance strategies of Black mothers, which open up new possibilities for Black educational futurity.